2011
DOI: 10.1002/app.34432
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ethylene‐propylene copolymers with high‐temperature gradient adsorption liquid chromatography and CRYSTAF

Abstract: Blends of linear polyethylene (PE) and isotactic polypropylene (iPP) with different average molar masses and a series of ethylene-propylene (EP) copolymers with different chemical composition as well as blends of PE, Ipp, and EP copolymers were separated using a carbon-column packing (HypercarbV R ) and gradients of 1-decanol or 2-ethyl-1-hexanol ! 1,2,4-trichlorobenzene (TCB). The separation is based on full adsorption of linear PE on the carbon sorbent at temperature 160 C. However, iPP is not adsorbed and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 58 publications
(53 reference statements)
0
38
1
Order By: Relevance
“…Independence of the elution volumes on the molar mass >15-20 kg/mol was also found for PE [164] and EP, EB, EO and ethylene/1-decene copolymers [161]. It is typical for adsorption phenomena that adsorption depends on the shape of a molecule, on positions and numbers of functional groups, on polarizability of the molecule, as well as on the type and nature of the sorbent and the solvents.…”
Section: Polyolefinsmentioning
confidence: 71%
See 2 more Smart Citations
“…Independence of the elution volumes on the molar mass >15-20 kg/mol was also found for PE [164] and EP, EB, EO and ethylene/1-decene copolymers [161]. It is typical for adsorption phenomena that adsorption depends on the shape of a molecule, on positions and numbers of functional groups, on polarizability of the molecule, as well as on the type and nature of the sorbent and the solvents.…”
Section: Polyolefinsmentioning
confidence: 71%
“…Macko et al demonstrated the usefulness of the approach for EPC [164] and copolymers of propylene with different tacticities [165]. Moreover, terpolymers of ethylene, propylene and a diene monomer (EPDM) were separated [166].…”
Section: Polyolefinsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the fact that all LCB elute in the same volume range as for the similarly constituted samples without LCB (PEL90 and PEL195) is a clear indication that the retention strength is driven by the presence of SCB (i.e., by the average ethylene sequence length) with an insignificant effect of the LCB junction. It was also shown [37] that linear PE with a molar mass > 14 kg/mol (14-1050 kg/mol) eluted in the 1-decanol/TCB/Hypercarb system with elution volumes which differed each from one another by about 0.2 mL. The elution volumes of the LCB PE samples also differ by about 0.2 mL each from one another ( Figure 2).…”
Section: Resultsmentioning
confidence: 91%
“…The separation in HT‐HPLC depends mainly on the chemical composition of the polyolefin and in EP copolymers separation is according to the ethylene content of the sample . Several studies had been done on HT‐HPLC of metallocene EP copolymers but their focus was on the bulk samples . Fractionation of metallocene EP copolymers by TREF and subsequent HT‐HPLC analysis has not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%